Implication of Viral Infections for Greenhouse Gas Dynamics in Freshwater Wetlands: Challenges and Perspectives - Bonetti, Giuditta; Trevathan-Tackett, Stacey M.; Carnell, Paul E.; Macreadie, Peter I. (Frontiers in Microbiology, 2019)
Viruses are non-living, acellular entities and the most abundant biological agents on earth. They are widely acknowledged as having the capacity to influence global biogeochemical cycles by infecting the bacterial and archaeal populations that regulate carbon and nutrient turnover. Evidence suggests that the majority of viruses in wetlands are bacteriophages, but despite their importance, studies on how viruses control the prokaryotic community and the concomitant impacts on ecosystem function (such as carbon cycling and greenhouse gas flux) in wetlands are rare. Here we investigate virus-prokaryote interactions in freshwater wetland ecosystems in the context of their potential influence on biogeochemical cycling. Specifically, we 1) synthesize existing literature to establish current understanding of virus-prokaryote interactions, focusing on the implications for wetland greenhouse gas dynamics; and 2) identify future research priorities. Viral dynamics in freshwater wetlands have received much less attention compared to those in marine ecosystems. However, based on our literature review, within the last ten years viral ecology studies on freshwater wetlands have increased 2-fold. Despite this increase in literature, the potential implication of viral infections on greenhouse gas emission dynamics is still a knowledge gap. We hypothesize that the rate of greenhouse gas emissions and the pool of sequestered carbon could be strongly linked to the type and rate of viral infection. Viral replication mechanism choice will consequently influence the microbial efficiency of organic matter assimilation and thus the ultimate fate of carbon as a greenhouse gas or stored in soils.